Nuclear Respiratory Factor 1 Negatively Regulates the P1 Promoter of the Peroxisome Proliferator-Activated Receptor-γ Gene and Inhibits Chicken Adipogenesis - Cui, Tingting; Xing, Tianyu; Huang, Jiaxin; Mu, Fang; Jin, Yanfei; You, Xin; Chu, Yankai; Li, Hui; Wang, Ning (Frontiers in Physiology, 2018)
Peroxisome proliferator-activated receptor-γ (PPARγ) is a master regulator of adipogenesis, and alterations in its function are associated with various pathological processes related to metabolic syndrome. Recently, we found that the chicken PPARγ gene is regulated by three alternative promoters (P1, P2 and P3), producing five different transcript isoforms and two protein isoforms. In this study, the P1 promoter structure was characterized. Bioinformatics identified six putative nuclear respiratory factor 1 (NRF1) binding sites in the P1 promoter, and a reporter assay showed that NRF1 inhibited the activity of the P1 promoter. Of the six putative NRF1 binding sites, individual mutations of three of them abolished the inhibitory effect of NRF1 on P1 promoter activity. Furthermore, a ChIP assay indicated that NRF1 directly bound to the P1 promoter, and real-time quantitative RT-PCR analysis showed that NRF1 mRNA expression was negatively correlated with PPARγ1 expression (Pearson’s r = –0.148, p = 0.033). Further study showed that NRF1 overexpression inhibited the differentiation of the immortalized chicken preadipocyte cell line (ICP1), which was accompanied by reduced PPARγ1 mRNA expression. Taken together, our findings indicated that NRF1 directly negatively regulates the P1 promoter of the chicken PPARγ gene and inhibits adipogenesis.